Levosimendan for the prevention of acute organ dysfunction in sepsis - Gordon,AC; Perkins,GD; Singer,M; McAuley,DF; Orme,RML; Santhakumaran,S; Mason,AJ; Cross,M; Al-Beidh,F; Best-Lane,J; Brealey,D; Nutt,CL; et al. (New England Journal of Medicine, 2016)
BACKGROUNDLevosimendan is a calcium-sensitizing drug with inotropic and other propertiesthat may improve outcomes in patients with sepsis.METHODSWe conducted a double-blind, randomized clinical trial to investigate whether levosimendanreduces the severity of organ dysfunction in adults with sepsis. Patientswere randomly assigned to receive a blinded infusion of levosimendan (at a dose of0.05 to 0.2 μg per kilogram of body weight per minute) for 24 hours or placeboin addition to standard care. The primary outcome was the mean daily SequentialOrgan Failure Assessment (SOFA) score in the intensive care unit up to day 28 (scoresfor each of five systems range from 0 to 4, with higher scores indicating more severedysfunction; maximum score, 20). Secondary outcomes included 28-day mortality,time to weaning from mechanical ventilation, and adverse events.RESULTSThe trial recruited 516 patients; 259 were assigned to receive levosimendan and257 to receive placebo. There was no significant difference in the mean (±SD) SOFAscore between the levosimendan group and the placebo group (6.68±3.96 vs.6.06±3.89; mean difference, 0.61; 95% confidence interval [CI], −0.07 to 1.29;P=0.053). Mortality at 28 days was 34.5% in the levosimendan group and 30.9%in the placebo group (absolute difference, 3.6 percentage points; 95% CI, −4.5 to11.7; P=0.43). Among patients requiring ventilation at baseline, those in the levosimendangroup were less likely than those in the placebo group to be successfullyweaned from mechanical ventilation over the period of 28 days (hazard ratio,0.77; 95% CI, 0.60 to 0.97; P=0.03). More patients in the levosimendan group thanin the placebo group had supraventricular tachyarrhythmia (3.1% vs. 0.4%; absolutedifference, 2.7 percentage points; 95% CI, 0.1 to 5.3; P=0.04).CONCLUSIONSThe addition of levosimendan to standard treatment in adults with sepsis was notassociated with less severe organ dysfunction or lower mortality. Levosim